The association between basilar artery wall thickness and posterior circulation ischemic stroke: insights from high-resolution vascular wall imaging in subclinical atherosclerosis - Zhang, Zhen; Yi, Lirong; Zhou, Jie; He, Xiaojing; Yuan, Mingjing; Xiang, Bo (Frontiers in Neurology, 2025)
Basilar atherosclerosis is a major cause of posterior circulation ischemic stroke and it can affect neurological function negatively. Little is known about subclinical atherosclerotic changes before plaque formation. However, imaging changes in atherosclerotic plaque rupture and thrombosis have been extensively studied, which are major factors leading to the development of stroke. This study included 51 patients with posterior circulation ischemic stroke, 55 patients with high-risk factors for atherosclerosis, and 36 patients without high-risk factors for atherosclerosis. Based on high-resolution vascular wall imaging (HR-VWI) data, we quantitatively analyzed the differences in morphological abnormalities of the basilar artery wall between the three groups, including wall thickness, wall area, vessel area, and lumen area. This study aims to investigate the impact of abnormal basilar artery wall morphology, particularly on arterial wall thickness, on posterior circulation stroke development and its potential utility as a predictive biomarker. The results revealed that the stroke group exhibited significantly higher rates of cardiovascular risk factors (diabetes, hypertension, and elevated LDL-C) and increased basilar artery wall thickness compared to the high-risk group (p < 0.05). Logistic regression identified previous stroke, diabetes, and increased wall thickness as independent stroke risk factors. ROC analysis revealed strong associations between posterior circulation ischemic stroke and both vessel wall thickness alone (AUC = 0.806) and its combination with clinical features (AUC = 0.841), indicating potential diagnostic utility. These findings highlight the association between basilar artery wall morphology and stroke, supporting its potential role in risk stratification.